Desarrollo del proceso de atención de enfermería en paciente con infarto agudo de miocardio en la cara anterolateral. - Espinoza Pincay, María Daylin (2019)
The clinical case presented below refers to the 67-year-old male older adult who was admitted to the emergency area for presumptive chest pain syndrome diagnosis. Patient reports that about 3 hours ago and after family discussion presents precordial pain of oppressive type, high intensity 8/10 on the scale of EVA, which radiates to the anterior region of the neck, front side of the shoulder and left arm, reason why which is transferred by relatives to the JULIUS DOEPFNER Hospital where he performs an electrocardiogram and suggests the admission, however the patient decides not to enter so prescribing aspirin and other medication that he does not remember. Approximately 2 hours ago the picture was exacerbated presenting dyspnea of small efforts, profuse diaphoresis and palpitations. Placing the definitive diagnosis as an acute myocardial infarction of the anterolateral side. It seems logical that the term acute myocardial infarction is applied when there is an exacerbation of health problems that shows a clear difficulty in the patient's deterioration when it is not treated in time. It is essential to know that not all patients are prone to suffer from this type of pathology but to exceptions such as those who lead a full and healthy life.